Clustering of cardiovascular disease risk factors in a rural adult population in Nigeria - Akubudike Alikor, Chizindu; Emem-Chioma, Pedro (International Journal of Research in Medical Sciences, 2018)
Background: Cardiovascular disease (CVD) is responsible for one third of global deaths and is the leading contributor to global disease burden. A non-communicable disease survey done in Nigeria helped determine the prevalence of major CVD risk factors in the country and showed a rising trend in the prevalence. This study aims to determine the proportion of adults in a rural farming community in the Niger Delta region of Nigeria with clustering of the following CVD risk factors: hypertension, diabetes, obesity, dyslipidaemia, hyperuricaemia, ECG-LVH, smoking, heavy alcohol consumption and physical inactivity. Methods: Descriptive cross-sectional survey carried out in a rural farming community in the Niger Delta region of Nigeria. Stratified sampling method was used to recruit study subjects aged 18 years and above and a total of 500 subjects completed the survey. Socio-demographic information, anthropometric, blood pressure and ECG measurements were obtained. Venous samples were collected and analyzed. Results: Five hundred subjects participated. There were 156 males and 344 females with male to female ratio of 1:2.3. The overall mean age was 41.32±17.0 with range of 18 years to 95 years. The mean age for males was 42.84±17.8 and females 40.62±16.6. Overall, 38.2%, of subjects had 2 or more risk factors. Additionally, 42.1% of males and 31.4% of females had ≥2 of these risk factors. Multivariate logistic regression showed higher clustering of risk factors with increasing age, male gender, Government staff and higher educational attainment. Conclusions: Clustering of CVD risk factors is high in this rural community of Nigeria and requires integrated approach to its prevention, detection and treatment.